The Creation Strategy of Rene Hu Dance as the Institutional Dance of the Papua Language Center - Ida Bagus Gede Surya Peradantha; Godlief Patrice Felixe Muabuay; Hana Naema Jarisetouw; Riska Kogoya; Yohanes Primus Boli (LPPM Institut Seni Indonesia Padangpanjang, 2025)
This study explores the creation process of Rene Hu, the official ceremonial dance of the Papua Language Center, through an artistic autoethnography perspective. The research is motivated by the institutional need for a representative work that bridges organizational identity with Papuan cultural heritage. The objective is to reflect and analyze creation strategies in the creative process while positioning performance art as a medium for institutional identity formation. The method employed is artistic autoethnography, combining participatory observation, interviews with cultural leaders and local artists, documentation, and the choreographer’s reflective notes. The creative process followed four stages: preparation, exploration, creation, and evaluation, engaging local communities, artists, students, and the initiating institution. The findings reveal that Rene Hu functions not only as an artistic product but also as a cultural strategy that connects Papuan traditions with institutional values through negotiation between an external choreographer and cultural custodians. This study contributes to the development of artistic research in Indonesia by offering a model of institutional dance creation that is ethical, representative, and sustainable, and by highlighting the potential of artistic autoethnography as a reflective approach in choreographic practice.